Analisis Fraud Diamond dalam Mendeteksi Kecurangan pada Laporan Keuangan pada Perusahaan Sektor Transportasi dan Logistik yang Listed di BEI Periode 2021-2024 - Jean Carmenita; Barlia Annis Syahzuni (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Financial statements are the primary tool for investors and stakeholders to assess a company's performance. However, manipulation of financial statements, which still frequently occurs, can result in information that does not reflect the actual condition, thereby increasing the risk of erroneous investment decisions, financial losses, and a decline in public trust in the capital market. Therefore, early detection of financial statement fraud is crucial. This study aims to provide empirical evidence regarding the relationship between internal pressure, external pressure, opportunity, rationalization, and capability on financial statement fraud. The research was conducted by applying panel data regression on 18 transportation and logistics companies listed on the IDX (Indonesia Stock Exchange) for the period 2021–2024. Statistical analysis employed a Fixed Effect Model, which was selected based on the Chow test and Hausman test. The selected model meets classical assumption tests. The results indicate that the sample data are suitable for analysis, and the partial influence of the variables on financial statement fraud shows that external pressure and rationalization have a negative significant effect on financial statement fraud. In contrast, internal pressure, opportunity, and capability do not have a significant effect. Future studies are recommended to include variables such as audit quality, changes in accounting policies, or audit opinions to better detect potential fraud on financial statement.